(untitled) (FULafia Journal of Science and Technology, 2021)
One of the greatest scourges of this era is air pollutants not only because of its impact on climate change but also of its impact on public a health. A mathematical model using the three dimensional fractional step method based on the discretization of the time dependent atmospheric advection diffusion equation for describing the dispersion of the air pollutants released from the source into the atmosphere was examined. Many pollutants that are major factors of diseases in humans such as Particulate Matter (PM), Nitrogen oxide (NO2), Sulphur oxide (SO2) and Carbon monoxide (CO) which penetrates the respiratory system via inhalation, causing respiratory and cardiovascular diseases, reproductive and central nervous system dysfunctions, as well as cancer were identified. The study revealed that the toxicity potential (TP) of the air pollutants (NO2, and PM) are at elevated level since NO2 have been shown to cause discomfort in vulnerable persons having asthma at just 0.1ppm. The implications of the results to public health management system are further discussed.